The Effect of Reaction Variations on Increasing the Reaction of SSB Gumarang's Goalkeepers - Ari Pratama Pulungan; Irwansyah Siregar (Jurnal Pendidikan Jasmani (JPJ), 2022)
This study aims to determine the effect of variations in reaction training on the increase in reaction speed of the 2019 Gumarang SSB goalkeeper. The research method used is an experimental method. This sample was taken by means of purposive sampling technique of 4 people. Furthermore, the overall sample was given the same treatment, namely doing exercise variations of reaction exercises. This research was conducted for 6 weeks, with a frequency of training 3 times a week. Hypothesis analysis, from the pre-test data and post-test data, the goalkeeper's reaction speed obtained tcount of 20.32. Furthermore, this value is compared with the ttable value with dk = n-1 (4-1 = 3) at the significant level = 0.05 is 3.18, thus tcount> ttable (20.32> 3.18). This means that H0 is rejected and Ha is accepted. The conclusion of this study is that there is a significant effect on the variation of reaction exercises on the increase in the reaction speed of the 2019 Gumarang SSB goalkeeper.